Internet connectivity disruption in Mexico (Mexico) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Mexico. Data sourced from IODA.
Network Disruption Incident ID: MX-2026-0032. Severity: critical. Confidence: 75%